PENGARUH LITERASI KEUANGAN, LINGKUNGAN SOSIAL DAN AJARAN TAMANSISWA ”OPOR BEBEK MATENG SAKA AWAKE DEWE” TERHADAP PENGELOLAAN KEUANGAN - Dewi Kusuma Wardani; Meita Dwi Lestari (Jurnal Manajemen Terapan dan Keuangan, 2023)
This study aims to analyze the effect of financial literacy, social environment, and Tamansiswa teachings "Opor Bebek Mateng Saka Awake Dewe" on financial management. This study uses a quantitative approach using primary data. The population in this study were students at the Tamansiswa University of Yogyakarta and the samples obtained were 111 respondents. Sampling used the accidental sampling method and IBM SPSS Statistics 20 for data analysis. The independent variables of the research are financial literacy, social environment and Tamansiswa teachings "Opor Bebek Mateng Saka Awake Dewe" while financial management is the dependent variable. The results of this study concluded that leuangan literacy has a positive effect on financial management, while the social environment and Tamansiswa teachings "Opor Bebek Mateng Saka Awake Dewe" have no effect on financial management.